Advances in Metabolic Profiling of Biological Samples - Pinto, Joana (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is a collection of articles belonging to the Special Issue Advances in Metabolic Profiling of Biological Samples of Metabolites. The Special Issue is dedicated to reviews and original articles covering the current methodological and technological advancements in the pre-analytical handling of biological samples, sample preparation protocols, analytical approaches for untargeted and targeted metabolic profiling, and metabolite annotation tools.